PENTINGNYA PROSES VERIFIKASI KESESUAIAN DATA PADA VERIFIKASI DATA UNTUK PERMOHONAN NOTAM - Muhammad Nabil Rahadinan; Elfi Amir; Endang Sugiharti; Rini Sadiatmi; Dini Wagini; Togi Adnan Maruli Sinaga; Novita Ayu Permatasari; Mochamad Faisal Muzaki (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
NOTAM is a notice disseminated by telecommunication that contains information about the establishment, condition, or change of facilities, services, procedures, or flight hazards, which must be known in a timely manner by personnel related to flight operations. The research method used is a qualitative research method in which the researcher studies how the group works in actual conditions through observation and interviews.  This research examines the importance of understanding NOTAM requirements in order to minimize the risk of accidents and improve flight safety. Various factors can influence the NOTAM application process, including complex aviation regulations, weather changes, airport conditions, and navigation information. Ignoring or misinterpreting these regulations may result in errors in aircraft operation, especially in emergency situations.